Pneumatic actuation of a firefighting robot: A theoretical foundation and an empirical study - Ajala, Mosud Taiwo; Khan, Md. Raisuddin; Salami, Momoh J. E; Shafie, Amir Akramin; Oladokun, Majeed Olaide; Iskandar Nor,, Mohamad (IEEE, 2020)
In recent times, the need for a self-powered, autonomous firefighting robot, which can cope in fire hot spots, is strongly required in fire emergencies. The obtainable firefighting robots lack efficient performance in such conditions due to less reliability of their electric-powered actuators in the high-temperature environment under fire emergency. Our previous study suggests a gas actuated propulsion system (GAPS) as an alternative to the identified limitations of the existing electric actuated propulsion system. The GAPS drives a carbon dioxide propelled autonomous firefighting robot (CAFFR), which uses dry ice as its power source. However, there still exists a lack of detailed understanding of the working principle of the proposed GAPS. Thus, this study provides a theoretical framework for the novel CAFFR. Upon establishing the working theory and the concept of the CAFFR, the research carried out an empirical analysis of the key influencing design parameters for the CAFFR pneumatic actuation. The study presents a mathematical model of the effects of the design parameters and after that, discusses its implications.